ANALISIS TENTANG PERSEPSI SOCIAL MEDIA MARKETING, KAMPANYE VIRAL MARKETING, DAN DINAMIKA VIRTUAL BRAND COMMUNITY PADA FITUR SPONSOR INSTAGRAM TERHADAP PEMBENTUKAN BRAND AWARENESS ADIDAS - Prakoso, Doni; Magnadi, Rizal Hari (Faculty of Economics and Business Diponegoro University, 2017)
Digitalization era of social media is now used as a tool for advertising. Where Instagram had established sponsors feature like Facebook ads. Starting from declining issues from adidas which created a research question: â€œHow does instagram sponsors feature shaped brand awareness of Adidas?â€. This study uses four variables: social media marketing perception, viral marketing campaign, and dinamics of virtual brand community to affected brand awareness. This research hypothesis testing using the data of 130 respondents. The analysis technique used in this research is to use a software program Statistical Package for Social Science (SPSS). The result of this study indicate social media marketing perception, viral marketing campaign, and dinamics of virtual brand community are positively affect to brand awareness.